DEATHS DUE TO COVID-19 AMONG BRAZILIAN NURSING WORKERS: A CROSS-SECTIONAL STUDY - Barreto, Márcio Adriano Fernandes; Pessoa, Graça Rocha; Queiroz Neto, João Bezerra de; Chaves, Edna Maria Camelo; Silva, Lucilane Maria Sales; Moreira, Thereza Maria Magalhães (Cogitare Enfermagem, 2022)
Objective: to analyze deaths due to COVID-19 in Brazilian Nursing professionals, with confirmed diagnoses of the disease and in quarantine, hospitalized or deceased, at the Federal Nursing Council Observatory. Method: a cross-sectional study conducted in Brazil between March 2020 and August 2021, via the Federal Nursing Council Observatory. The data were analyzed using descriptive and inferential statistics. Results: the prevalence of death due to COVID-19 in Brazilian Nursing professionals was 2.5% (825/32,560) and 4.9% (109/2,224) in nursing assistants, these latter with a higher mean age (p<0.0001). Although 84.5% (27,508/32,560) of the sample was female, the percentage of deaths was higher in the male gender, with 5.2% (263/5,052) (p<0.0001). The logistic regression analysis showed that gender and professional category can predict deaths due to COVID-19 among Brazilian Nursing workers. Conclusion: the study contributes to evidencing the risks faced by the professional category in coping with COVID-19, as well as to rethinking measures to reduce the harms imposed by the pandemic on this population segment.